Psychotherapy and psychological consulting in rehabilitation programs of psychoactive substances abused - Маркова, Маріанна Владиславівна; Савіна, Майя Василівна; Антонович, Мілєна Олександрівна (Psychiatry, Neurology and Medical Psychology, 2019)
Psychotherapy and psychological counseling in narcology are an important component of the therapeutic and prophylactic process and are used in the complex of rehabilitation measures. Is inseparable from medication, physiotherapy and psychosocial effects, begins at the earliest stages of treatment. The use of psychotherapy in the rehabilitation phase of chemically dependent persons is necessary and promising. Effective psychotherapeutic programs involve the use of a whole range of psychotherapeutic approaches that include various methods and forms of psychotherapy that are used by the community of specialists in unison with the complex of psychopharmacotherapy and other non-drug therapies. Each separate strategic stage of rehabilitation of substance addicts corresponds to a specific psychotherapeutic method. Psychotherapeutic rehabilitation measures in narcology should be personality-oriented, differentiated and comprehensive, including both psychotherapeutic rehabilitation measures and drug-centered rehabilitation approaches. In stages, the introduction of elements of the psychotherapy-rehabilitation approach, which is necessary from the very beginning, at the stage of acute conditions. If successful  psychotherapy optimizes the totality of personal statuses seeking their harmonious disclosure and fixing the position of the individual in the desired statuses. The basic principles of psychotherapy abusing on surfactants are considered in unison with the modern concepts of treatment in general and include volunteering, individuality, complexity and refusal to use psychoactive substance.